ISSUES OF SELECTING THE APPLICABLE NATIONAL LAW TO THE LABOR CONTRACT: EXPERIENCE OF THE REPUBLIC OF KAZAKHSTAN AND FOREIGN COUNTRIES - Z.B. Zhukova,; O.V. Miroshnikova,; E.A. Bryzgalova,; M.N. Myrzakhanova, (Academic Journal of Physical and Chemical Sciences, 2019)
According to the authors, the issues of choosing the applicable national law to an employment contract in Kazakhstan has a big difference compared with foreign countries, in particular with developed countries. In general, there are a number of problems that, when compared with international standards, reveal weaknesses in the legal framework, the term of the employment contract with the executive body should be regulated separately from other categories of workers. The time limits for the application of disciplinary measures to managers should be extended. An example is given of the choice of applicable national law to an employment contract in the Republic of Kazakhstan, which despite the differences with the labor laws of the EU countries, nevertheless, there is a tendency towards a convergence of the provisions of national labor laws.